Investigating the effect of education based on PRECEDE-PROCEED model on the preventive behaviors of musculoskeletal disorders in a group of nurses - Rakhshani, Tayebeh; Limouchi, Zeinab; Daneshmandi, Hadi; Kamyab, Amirhossein; Jeihooni, Ali Khani (Frontiers in Public Health, 2024)
Background One of the most important occupational complications that could occur in nurses is musculoskeletal disorders. In this study, we designed an educational intervention based on the PRECEDE-PROCEED model to investigate its effects on a group of nurses on preventive behaviors of musculoskeletal disorders. Methods A total of 120 nurses working in Izeh City, Iran, participated in this semi-experimental study. The sampling was performed through a convenient sampling method, and the participants were randomly assigned to the experimental and control groups (60 participants for each group). Both groups filled out a questionnaire based on the PRECEDE-PROCEED model before and 2 months after the educational program as part of the data collection process. The data were examined using a paired t-test, an independent t-test, and a chi-square test after being entered into SPSS version 24. Results According to the findings, prior to the intervention, there was no difference between the two groups in terms of their knowledge (p = 0.221), attitude (p = 0.136), enabling factors (p = 0.325), reinforcing factors (p = 0.548), self-efficacy (0.421), and behavior (0.257) levels. However, following the intervention, a substantial rise was witnessed in the experimental group in each of the mentioned variables (p = 0.001). Conclusion In the current study, education based on the PRECEDE-PROCEED model led to the improvement of knowledge, attitude, enabling and reinforcing factors, self-efficacy, and finally preventive behaviors with musculoskeletal disorders in the participants. Considering the importance of the role of health education in promoting behaviors related to musculoskeletal disorders in nurses and the importance of observing related behaviors in preventing long-term complications, the necessity of education in a wider dimension and with different tools is felt more and more in society. Therefore, longer interventions with this aim could be carried out on nurses and other healthcare personnel.